Vigas mistas fabricadas com aço formado a frio usando conexões por aderência - Ferreira, Josyverton Gomes (2022)
Precast composite structures, mainly steel and concrete, have gained prominence, as they seek more rationalized solutions for civil construction, with advantages such as reduced waste of materials, reduced execution time and better-quality control of constructions. However, to ensure an efficient transfer of efforts between materials, an effective connection is necessary, capable of generating a high degree of interaction. Thus, this work was divided into 3 stages in order to study new connections arrangements by adherence in composite steel and concrete beams constituted by cold-formed steel using precast slabs. The first stage consisted of conducting a systematic review with the aim of quantitatively and qualitatively studying the main parameters of composite structures that used a cold formed steel, in order to assess which connection was more effective in transferring efforts. In the second stage, from experimental tests of flexion and dynamic tests, two distinct adherence connections arrangements were studied using checkered plate and a third model with a plain connector, in order to compare and identify the real contribution of the plate grooves chess. Furthermore, numerical models were created to calibrate the interfaces proposed in the experimental tests, in order to validate and allow a better evaluation of the mechanical behavior of the interfaces. Finally, it was observed that the arrangements with adherence connection presented sufficient performance to guarantee the effectiveness of the connection between the slab and the steel, and the grooves significantly participated in this contribution.